Development of an interactive e-module based on a case method to improve higher-order thinking skills - Firmansyah, Firmansyah; Irnandi, Irfan; Siregar, Nahrun Najib; Simamora, Ebeneser Wacner (Journal of Research in Instructional, 2023)
The objective of this study is to create a case-method-based interactive e-module that will enhance the higher-level thinking skills (HOTs) of students. Research and Development (R&D) utilizing the ten-step Borg & Gall model development constitutes this research method. This investigation is restricted to the seventh stage. This study's participants were FKIP UNIPA first-semester students enrolled in instructional mathematics courses. The sample for the study was determined by cluster random sampling. The participants in this research were partitioned into two groups: the experimental group consisted of students majoring in English education, while the control group comprised students majoring in Indonesian language education. In this study, questionnaires, interviews, validator assessment forms, and HOTs tests were utilized to collect data. Three data analysis techniques were utilized in this study: validity, practicability, and effectiveness. The outcomes demonstrate the e-module's validity. The practicality assessment yielded an 81.44% response rate from students in the very practical category. The HOTs of the pupils in the experimental class were superior to those of the control class. The mean HOTs of students in the control group were 67.67, whereas those in the experimental group have an average HOTs of 75.50.